2019
DOI: 10.24018/ejbmr.2019.4.5.84
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workplace Safety and Health Practices on Employee Commitment and Performance in Steel Manufacturing Companies in Rwanda

Abstract: The purpose of this study was to establish the effects of workplace safety and health practices on the employees’ commitment and performance in Steel manufacturing companies in Rwanda. The target population of this study was 533 people, which comprised of Managers, Supervisors and employees. A simple random sampling technique was used to select a sample size of 229 respondents from the target population. The data was collected using questionnaires, interview guide and personal observation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
2
10
0
Order By: Relevance
“…Adequate safety and health training could lead to a significant improvement in the capabilities of employees which will have a multiplier effect on employee skills and efficiency thereby improving productivity and performance of the firm (Michael et al, 2006). Further, Umugwaneza et al (2019) indicated that enhanced and consistent health and safety training could lead to a significant reduction in accident rate, material wastages, absenteeism, and compensation to hospitalize employees' thereby improving workers efficiency, productivity, and the firm's profitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate safety and health training could lead to a significant improvement in the capabilities of employees which will have a multiplier effect on employee skills and efficiency thereby improving productivity and performance of the firm (Michael et al, 2006). Further, Umugwaneza et al (2019) indicated that enhanced and consistent health and safety training could lead to a significant reduction in accident rate, material wastages, absenteeism, and compensation to hospitalize employees' thereby improving workers efficiency, productivity, and the firm's profitability.…”
Section: Discussionmentioning
confidence: 99%
“…According to Boyle (2012), knowledge of safety education is vital in identifying and managing dangers in the workplace adequately. Training has been identified as an impeccable aspect of any safety management in the organization and helps build workers' capacity to work based on safety guidelines (Umugwaneza, Nkechi & Mugabe, 2019). Similarly, a standard method to inspire good work behavior is for the organization to put in place a safety education and training program.…”
Section: Health and Safety Trainingmentioning
confidence: 99%
“…The projected benefit of this finding is that the number of companies that have HSE division and HSEMS certificate also estimated to increase. Companies that did not have proper HSE management could effect on decreasing the worker's productivity [17]. The increased of compliance in companies that did not have a HSE division or HSEMS certificate during COVID-19 explained that the company was trying to maintain the workers' productivity during a pandemic.…”
Section: Health and Safety Increase In Compliance Based On Respondentmentioning
confidence: 99%
“…Poor lighting is a minor issue as far as causes of OHS hazards at the workplace are concerned considering the mean score of 1.9. Heryati, Menzata Z and Afriyani (2019); Umugwaneza, Nkechi, and Mugabe (2019); Mwangi and Waiganjo (2017) establish that regular education and training, using an integrated approach, can promote positive attitude of employees towards occupational health and safety, mitigate or prevent workplace injuries, and also influence positively and dominantly employee performance. Umugwaneza, Nkechi, and Mugabe (2019) additionally support the finding that adequate provision of personal protective equipment reduce workplace injuries and accidents.…”
Section: Gender Of Respondentsmentioning
confidence: 99%
“…In addition to providing a satisfying work environment and healthy workplace concept, adherence to occupational safety and health regulations enhances employee work satisfaction and positive work outcomes (Perera, 2019;Oluoch, 2017). Effective management of health and safety at the workplace usually influences significantly and positively organisational commitment and productivity; impacts workers attitude positively towards work and gives them a more positive impression about their health and security (Umugwaneza, Nkechi & Mugabe, 2019;Kaynak et al, 2016;Yeh, 2014;DeJoy et al, 2010;Ward et al, 2008). It is further asserted that organisations that invest massively in safety management system and practices are better placed to promote occupational safety, reduce/prevent job-related accidents, and improve employee as well as organisational performance (Wambulwa et al, 2018;Wachter &Yorio, 2014;Dwomoh et al, 2013;and Oxenburgh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%